The complex researches of structure and function of Antarctic terrestrial microbial communities - O. B. Tashyrev (Ukrainian Antarctic Journal, 2009)
Complex researches on studying structure and functions Antarctic microbial communities and formation of plural mechanisms of adaptation of microorganisms to extreme environmental factors of Antarctic are carried out. As model ecosystems subpolar thermostatic oases on the islands located in passages Lemaire and Penola along coast of Antarctic peninsula (a zone 30 x 60 km) are used. For the first time presence in environments of subpolar thermostatic Antarctic oases (including on vertical rocks) microorganisms, resistant to UV- radiation, antibiotics and toxic metals is shown. Obtained data testify to an opportunity of development on the basis of extremophilic microorganisms the express-indicator systems for an estimation of influence of climatic factors on functioning of Antarctic biota. With use of GIS-systems and 3D-models the integrated models of microbial communities' adaptation to extreme climatic factors are developed. Original positions about functioning ice algal-bacterial communities which apparently, play an essential role in formation of global vector streams of biogenic elements and balance of hotbed gases are formulated.